# Solve for u -24=-6/5u -24=-65u
Rewrite the equation as -65u=-24.
-65u=-24
Multiply both sides of the equation by -56.
-56⋅(-65)⋅u=-56⋅-24
Simplify both sides of the equation.
Simplify -56⋅(-65)⋅u.
Cancel the common factor of 5.
Move the leading negative in -56 into the numerator.
-56⋅(-65)⋅u=-56⋅-24
Move the leading negative in -65 into the numerator.
-56⋅-65⋅u=-56⋅-24
Factor 5 out of -5.
5(-1)6⋅-65⋅u=-56⋅-24
Cancel the common factor.
5⋅-16⋅-65⋅u=-56⋅-24
Rewrite the expression.
-16⋅-6⋅u=-56⋅-24
-16⋅-6⋅u=-56⋅-24
Cancel the common factor of 6.
Factor 6 out of -6.
-16⋅(6(-1))⋅u=-56⋅-24
Cancel the common factor.
-16⋅(6⋅-1)⋅u=-56⋅-24
Rewrite the expression.
-1⋅-1⋅u=-56⋅-24
-1⋅-1⋅u=-56⋅-24
Multiply.
Multiply -1 by -1.
1⋅u=-56⋅-24
Multiply u by 1.
u=-56⋅-24
u=-56⋅-24
u=-56⋅-24
Simplify -56⋅-24.
Cancel the common factor of 6.
Move the leading negative in -56 into the numerator.
u=-56⋅-24
Factor 6 out of -24.
u=-56⋅(6(-4))
Cancel the common factor.
u=-56⋅(6⋅-4)
Rewrite the expression.
u=-5⋅-4
u=-5⋅-4
Multiply -5 by -4.
u=20
u=20
u=20
Solve for u -24=-6/5u

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top